2020
DOI: 10.3390/ijerph17239070
|View full text |Cite
|
Sign up to set email alerts
|

Time Management by Young People in Social Difficulties: Suggestions for Improving Their Life Trajectories

Abstract: This article covers the responses provided by professional practitioners in socio-educational intervention who are responsible for young people in social difficulties, in other words those facing personal and social issues that stop them from leading a normal life. It considers their suggestions for helping young people to better their lives by becoming autonomous, as well as to manage and use their time in their transition to adulthood. A qualitative study was conducted that used an open, ad-hoc questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
4
0
2
Order By: Relevance
“…The professionals must believe in the potential of youth participation and attempt to overcome the obstacles to participation. Participation is not only limited to defining the goals of the socio-educational project (Fernández-Simo & Cid, 2018 ) but should also promote meaningful community involvement, as an indicator of the quality of the protective action and the means for personal development during the preparation for adult life (De-Juanas et al, 2020 ). The bureaucratic organization of the system itself is prioritized to the detriment of youths’ ability to decide such important aspects as the time of exit from the residential resource.…”
Section: Discussionmentioning
confidence: 99%
“…The professionals must believe in the potential of youth participation and attempt to overcome the obstacles to participation. Participation is not only limited to defining the goals of the socio-educational project (Fernández-Simo & Cid, 2018 ) but should also promote meaningful community involvement, as an indicator of the quality of the protective action and the means for personal development during the preparation for adult life (De-Juanas et al, 2020 ). The bureaucratic organization of the system itself is prioritized to the detriment of youths’ ability to decide such important aspects as the time of exit from the residential resource.…”
Section: Discussionmentioning
confidence: 99%
“…En otro orden, la percepción de los profesionales y de los jóvenes del estudio evidencian la ausencia de referentes adultos fuera del tejido institucional (De-Juanas et al, 2020). Asimismo, se denota una red social de apoyo constituida, principalmente, por otros jóvenes conocidos durante su trayectoria en el sistema de protección.…”
Section: Discussionunclassified
“…Así, McKee y Heydon (2015) y Sáenz et al ( 2020) sitúan los programas intergeneracionales entre las medidas más pertinentes para unir generaciones, puesto que la investigación ha demostrado que estos ofrecen múltiples oportunidades para promover la interdependencia y cooperación intergeneracional. Esto implica involucrar a estos jóvenes en diferentes actividades y mecanismos sociales en espacios de relaciones intergeneracionales inclusivos, que les permitan adquirir capital social (Almqvist y Lassinantti, 2018;Jardim y Marqués da Silva, 2018;Pieris, 2020;Rodríguez y Vidal, 2015) como medio ante un aislamiento que parte de la desconfianza hacia el propio sistema y entorno en el que viven (De-Juanas et al, 2020).…”
Section: Introductionunclassified
“…The transition to employment is made more difficult by poor educational outcomes (Arnau-Sabatés, 2015;De-Juanas, 2020). Research has long demonstrated the benefits of education include better physical and mental health, avoidance of risk behaviours, lower rates of unemployment and increased earning potential, particularly post-secondary education (Harrison, 2020).…”
Section: Educationmentioning
confidence: 99%